Designs, formats and applications of lateral flow assay: A literature review - Sajid, Muhammad; Kawde, Abdel-Nasser; Daud, Muhammad (Journal of Saudi Chemical Society, 2015)
This manuscript provides a brief overview of latest research involving the use of lateral flow assay for qualitative and quantitative analysis in different areas. The excellent features and versatility of detection formats make these strips an ideal choice for point of care applications. We outline and critically discuss detection formats, molecular recognition probes, labels, and detection systems used in lateral flow assay. Applications in different fields along with selected examples from the literature have been included to show analytical performance of these devices. At the end, we summarize accomplishments, weaknesses and future challenges in the area of lateral flow strips.